If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(3x + 2) = 23 Reorder the terms: X(2 + 3x) = 23 (2 * X + 3x * X) = 23 (2X + 3xX) = 23 Solving 2X + 3xX = 23 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: -23 + 2X + 3xX = 23 + -23 Combine like terms: 23 + -23 = 0 -23 + 2X + 3xX = 0 The solution to this equation could not be determined.
| y=29-4(4) | | 4/5=x-3/9 | | 7[x+(11)]+(-3)=-53 | | 2/5(d-3)=30 | | y=29-4(1) | | 6x-30=x-25 | | 9g-15=21 | | 3.4x=1.8x+2.5 | | 5x-6+2x=9x-7 | | 9j^2+42j+49=0 | | 3x^2+15x-9.1=0 | | h=3(1)+1 | | 0.2c+0.08c-3.6c=0 | | 9=9-11x | | 0.3(y+2)=24 | | 10z^2-1440=0 | | 28-2u=5u | | 2x+14=-5x-11 | | -5/4m-1/6=7/3 | | 4x-2=7-2x | | 8+3x-9x=20 | | 0=1-x+y | | 12x+3x-7=4x+31 | | 3x+3*(-3)=3 | | 5x+8+x=170 | | h=3(0)+1 | | 3x+3*3=3 | | -16h^2-49h-3=0 | | h=3(-2)+1 | | 3*(-2)+3y=3 | | h=3(-1)+1 | | .3(3z+7)+18.9=.5(3z-6) |